PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN UMUM (PERUM) BULOG KANTOR CABANG SURAKARTA - Ika Fitri Jumiati; Alwi Suddin; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the influence of the work enviroment, motivation and work discipline on employee performance at the Public Corporation (Perum) BULOG Surakarta Branch Office. This study uses survey methods, the type of data used are qualitative and quantitative data, the source of the data used are primary data and secondary data. The total population in this study was 40 people. In this study because the population is less than 100, the sampling technique is saturated or census sampling, which is the technique of determining the sample when all members of the population are used. Data collection techniques in this study used a questionnaire. Data analysis techniques used, Descriptive Analysis, Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, F Test (Model Accuracy), and Determination Coefficient Test (R2). The results of this study concluded that the work environment has a significant effect on employee performance at the Public Corporation (Perum) BULOG Surakarta Branch Office. Motivation has no significant effect on employee performance at the Public Corporation (Perum) BULOG Surakarta Branch Office. Work Discipline has a significa effect on employee performance at the Public Corporation (Perum) BULOG Surakarta Branch Office.